PENERAPAN DISIPLIN UNTUK MENINGKATKAN MINAT BELAJAR BAHASA INDONESIA SISWA KELAS III SD NEGERI 94 BEBA - Andi Naila Aufa Tsabita; Yuliana; Iskandar; Frisjenny Ceydar (STKIP Subang, 2026)
This study aimed to improve discipline and interest in learning Indonesian in third-grade students at SD Negeri 94 Beba through interactive and engaging learning strategies. The results showed an increase in discipline after consistent classroom rules were implemented, as well as an increase in interest in learning through the use of varied media and methods. Both aspects positively impacted student learning outcomes.